IDEAL framework in surgical innovation applied on laparoscopic niche repair. (August 2017) - Nikkels, C.; Vervoort, Anke J.M.W.; Mol, Ben Willem; Hehenkamp, Wouter J.K.; Huirne, Judith A.F.; Brölmann, Hans A.M.
Abstract: The research objective of the current systematic literature review is to classify the laparoscopic niche repair according to the IDEAL framework of 'innovation stages' and to recommend the required research setting to facilitate safe and properly timed implementation of the technique. In doing so, we are also able to evaluate the practical applicability of the IDEAL framework. A systematic search of the available literature on laparoscopic niche repair was performed in PubMed, Embase, and the Wiley/Cochrane library. Articles were classified according to the IDEAL framework and recommendations were given on additional required research before the technique can be safely implemented. Practical applicability of the IDEAL framework was also evaluated. Introduction of laparoscopic niche repair matches Idea (1) and Development (2a), according to the stages of IDEAL framework, although most studies are retrospective and complications have not been registered structurally in a considerable number of the articles. As feasibility and safety have been more or less established and surgery has been further developed we enter stage 2b (Exploration) and need prospective trials preferably comparing the effectiveness of laparoscopic niche repair to expectant management, the current standard care. Available studies were classified with the use of the IDEAL framework, achieving an overall IDEAL stage to be 2a Development. As clinical outcomes, though poorly registered, have been substantially improved, laparoscopic niche repair needs to be carried forward by more advanced study designs.